Managerial economics - Dean, Joel. (Englewood Cliffs, N.J. : Prentice-Hall, 1951)
The purpose of the book is to how economic analysis can be used in formulating business policies.
Includes bibliographical footnotes and index.
obn 23/01/2019
Loans
Keywords: Managerial economics